Coronary angiography and percutaneous coronary intervention in cardiac arrest survivors with non-shockable rhythms and no STEMI: A systematic review. (October 2019) - Harhash, Ahmed A.; Huang, Jennifer J.; Howe, Carol L.; Hsu, Chiu-Hsieh; Kern, Karl B.
Abstract: Background: Emergency coronary angiography (CAG) and percutaneous coronary intervention (PCI) are thought to improve outcomes in cardiac arrest (CA) survivors with ST segment elevation myocardial infarction (STEMI) and those without STEMI but likely cardiac etiology (shockable rhythms). However, the role of CAG ± PCI in OHCA survivors with non-shockable rhythms and no STEMI post-resuscitation remains unclear. Methods: We searched Ovid/MEDLINE, Embase, Scopus, the Cochrane Central Register of Controlled Trials, Web of Science, and ClinicalTrials.gov from inception to January 2019. Two reviewers independently screened titles and abstracts of all records retrieved in the database searches and full texts of all articles selected in the title/abstract screen, with disagreements resolved by consensus. Risk of bias was assessed using the Strobe checklist. Results: Fourteen out of 1174 articles met criteria for full review. Only two studies including 152 patients with confirmed non-shockable rhythms and no STEMI post resuscitation met all criteria and were analyzed. One study reported 97 patients (of 1497 in the registry) underwent CAG and 24.7% underwent PCI. The second study reported 55 patients (of 545 in the cohort) underwent CAG and acute coronary lesions were found in 16.4% but only 9.1% underwent PCI and no survival benefit was demonstrated. Conclusions: There is limited data describing the prevalence of CAD and the role of CAG ± PCI in CA survivors with non-shockable rhythms and no STEMI post-resuscitation. In the two studies meeting criteria for this systematic review, 16% of patients with non-shockable rhythms underwent PCI.